Research on the measurement of China's emergency management capabilities for public health emergencies and their driving factors - Li Yuan; Xiaocheng Gan; Kexin Zhang; Qianxi Zhang; Xie Yuan (Frontiers in Public Health, 2026)
Enhancing regional emergency response capabilities for public health emergencies poses a major challenge for China, which is undergoing rapid urbanization. Based on an analysis of the theoretical framework of emergency management for public health emergencies, this paper constructs an evaluation system comprising four dimensions: prevention and monitoring, emergency response, recovery and reconstruction, and emergency support. It employs the entropy weighting method to measure the emergency management levels of 285 prefecture-level cities in China from 2011 to 2024, utilizes the Dagum Gini coefficient and kernel density estimation to analyze regional disparities and dynamic evolution, and adopts the spatial Durbin model to investigate the spatial effects of driving factors. The study found that the index of emergency management levels for public health emergencies in China shows an overall upward trend but with a slow growth rate, rising from 0.037 during the 12th Five-Year Plan period to 0.048 during the 14th Five-Year Plan period. Spatially, it exhibits a gradient distribution characterized by “higher in the east and lower in the west, higher in the south and lower in the north,” with the eastern and southern regions showing a significant lead. Regional disparities have remained at high levels and continue to widen, with the overall Gini coefficient rising from 0.4836 to 0.5285; inter-regional disparities are the primary source, followed by intra-regional disparities, and the kernel density curve indicates that polarization is deepening. Among the driving factors, digital infrastructure and the level of technological innovation are core positive drivers, both exhibiting significant local promotion effects and positive spatial spillover effects; The overall effect of financial development is significantly negative, primarily due to negative spatial spillovers, reflecting the inhibitory role of cross-regional siphoning of financial resources; competition among local governments constrains neighboring regions through negative spatial spillovers; human capital levels have only a weak positive effect locally, while market openness has no significant impact. Regional heterogeneity is pronounced: the eastern region is driven by both digital infrastructure and technological innovation, with the strongest spillover effects; in the central region, technological innovation and human capital play key roles, while local government competition exhibits negative local effects; in the western region, the driving effect of digital infrastructure is not significant, but financial development has a positive indirect effect; in the northeastern region, digital infrastructure only has a local promotional effect and lacks spillover effects. Strengthening interregional coordination and expanding positive spillover effects are important pathways for improving emergency management capabilities.